Nepal Development Update, April 2018 - World Bank Group (World Bank, Kathmandu, 2018)
The Nepal Development Update is produced twice a year with the following two main aims: to report on key economic developments over the preceding months, placing them in a longer-term and global perspective; and to examine (in the Special Focus section) topics of particular policy significance. The Update is intended for a wide audience including policy makers, business leaders, the community of analysts and professionals engaged in economic debates, and the general public.